Study of the suitability of jetty facilities to the number of vessels on Kutaraja fishing port, Banda Aceh. Issue 1 (February 2021) - Chaliluddin, M A; Pujanna, A D; Iqbal, T H; Thaib, R; Kandi, O
Abstract: The jetty of the Kutaraja fishing Port which has been built at this time is not in accordance with the number of fishing vessels currently available, there are still many vesel moored in the Krueng Aceh river basin. The length of the jetty is a basic facility that determines the carrying capacity of the fishing port. The purpose of this research is to assess the suitability of the jetty facilities to the number of fishing vessel moored at Kutaraja fihing port to assess the capacity and determine the suitability of the currently available jetty. This research uses a descriptive method that is survey, namely by making direct observations of objects in the form of jetty and vessel. Based on the calculation of the ideal length of the jetty, the current requirement for the jetty of Kutaraja fishing port based on the calculation of the number of fishing vessels is 1.177 m. The length of the jetty of the Kutaraja fishing port that has been built at this time is not suitable, it is necessary to add a jetty of 836 m. Based on the results of this study, it is highly recommended to arrange a mooring pattern at the mooring jetty so that no more vessel moor in the river basin.